EFEKTIVITAS TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP INTENSITAS MEROKOK PADA SISWA SMPN 3 CERENTI - Dilla Aulia; Arneliwati Arneliwati; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Adolescents have high curiosity and always want to try something new. This causes adolescent tend to be smoking. There are some ways  that can be held to overcome smoking behavior one of them is therapy spiritual emotional freedom technique (SEFT). The aim of this research is to identify Effectiveness of spiritual emotional freedom technique (SEFT) therapy to decrease with smoking in adolencents. The design of this research is pre experiment with one group pretest posttest. This research was conducted in SMPN 3 Cerenti with total sample of 34 respondents. The sampling technique used proportionate stratified random sampling. Measuring instrumen used questionnaire sheets. The analysis used univariate analysis and bivariate using wilcoxon sign rank test. The mean number of smoking itensity before intervention was given 6,15 cigarettes and after intervention during six days the mean number decreased to 4,47 cigarettes. Statistical test results showed significant decrease in smoking intensity with p value 0,000 < α (0,05). The therapy of SEFT had effective on smoking intensity in adolescents. It is expected that this approach can be alternative to lessen the smoking behavior in adolescents.  Keywords : Adolescent;, SEFT therapy; smoking intensity.